Implementasi Strategi Bersaing Generik yang Terintegrasi dengan Service Marketing Triangle pada KFC Jember - Bimantoro, Satria (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This research was motivated by the high level of competition among fast food restaurants in the Jalan Gajah Mada area, Jember, characterized by numerous competitors within a short radius. Despite this situation, KFC Jember has managed to maintain its existence by implementing a competitive strategy that focuses not only on products but also on customer experience-based services. This study aims to analyze the implementation of generic competitive strategies integrated with the service marketing triangle to create a competitive advantage. This study used a qualitative approach, with data collection techniques including moderated participant observation, semi-structured interviews, and documentation until saturation point was reached. Data analysis employed domain and taxonomic analysis, while data validity was tested through source and technique triangulation.The results indicate that KFC Jember follows a centralized strategy while maintaining local marketing flexibility, thus maintaining brand presence and adaptively increasing sales. KFC Jember implements a low-cost leadership strategy through cost efficiency and evaluation, a differentiation strategy through a variety of services and products, and a differentiation focus strategy targeting all Jember consumers. Furthermore, these strategies are integrated with the service marketing triangle, which encompasses external, internal, and interactive marketing. This integration is a supporting factor in creating the company's competitive advantage.
Validasi 26 Mei_Reva_Dila
Keywords: competitive strategy; competitive advantage; service marketing triangle